PELAKSANAAN PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KEPENGHULUAN LABUHAN TANGGA KECIL KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Ramadhan, Egi Kurniawan; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Labuhan Tangga Kecil Village, Bangko District, Rokan Hilir Regency, still has several obstacles, as evidenced by the fact that what is happening in the field is that there are still Beneficiary Families (KPM) of Non-Cash Food Assistance (BPNT) who are truly entitled but do not receive it. On the other hand, there are Beneficiary Families (KPM) who are not entitled to receive Non-Cash Food Assistance (BPNT) and also aid recipients who have data that does not match, such as the same KK number so that the aid does not match the recipient data that has been recorded. This research aims to determine the effectiveness of the implementation of the Non-Cash Food Assistance Program (BPNT) in improving the welfare of the community in the Labuhan Tangga Kecil Subdistrict and to find out what are the obstacles to the Non-Cash Assistance Program (BPNT) in improving the welfare of the community in the Labuhan Tangga Kecil Subdistrict. The theory used in this research is the BPNT (Non-Cash Social Assistance Distribution Implementation Control Team) Guide regarding the effectiveness of assistance which consists of right target, right price, right quantity, right time and right quality. The data collection techniques used in this research were questionnaires, interviews and documentation. This research was carried out in the Labuhan Tangga Kecil District, Bangko District, Rokan Hilir Regency. The results of this research indicate that the implementation of the Non-Cash Food Assistance program in the Labuhan Tangga Kecil District, Bangko District, can be said to have been implemented effectively. This can be seen from the number of recipients who received assistance and the number of poor people in the Labuhan Tangga Kecil Penghuluan, Bangko District. However, there is still an inaccuracy in targeting recipients of the aid program, where there are KPM who are considered capable but are still registered as beneficiaries of the Non-Cash Food Assistance program. This happens because there is still a lack of monitoring by the task force and village officials towards the community and errors in collecting data. Keywords: Implementations, Non-Cash Food Assistance (BPNT), Welfare